Association Between Mental Health Disorders and Sexual Dysfunction in Patients Suffering from Rheumatic Diseases. (14th August 2014) - Anyfanti, Panagiota; Pyrpasopoulou, Athina; Triantafyllou, Areti; Triantafyllou, Georgios; Gavriilaki, Eleni; Chatzimichailidou, Sofia; Gkaliagkousi, Eugenia; Petidis, Konstantinos; Aslanidis, Spyros; Douma, Stella
Abstract Introduction Sexual functioning may be notoriously affected in patients suffering from rheumatic diseases, yet the extent to which physical and/or psychological factors contribute to sexual dysfunction in this particular group of patients remains underinvestigated. Aim This cross‐sectional study aimed at investigating whether an association exists between psychological status (anxiety, depression) and sexual dysfunction, independently of other physical factors, in patients with rheumatic disorders. Methods A total of 509 consecutive rheumatologic patients, aged 54.7 ± 14.2 years, 423 female and 86 male, were studied. Female and male sexual function was evaluated with the Female Sexual Dysfunction Index (FSFI) and the International Index of Erectile Function (IIEF) questionnaire, respectively. The Hamilton Anxiety Scale and the Zung Self‐Rating Depression Scale were used to detect presence of anxiety and depression, respectively. Main Outcome Measures Sexual dysfunction affected 69.9%, anxiety 37.5%, and depression 22% of our patients. Results A strong and negative correlation was found between anxiety and both FSFI (r = −0.169, P < 0.001) and IIEF score (r = −0.304, P = 0.004). Similarly, depressive symptomatology was strongly and negatively correlated with both FSFI (r = −0.178, P < 0.001) and IIEF score (r = −0.222, P = 0.04). In the logistic regression analysis, apart from increasing age and female sex, depression (P = 0.027) and anxiety (P = 0.049) were identified as the only predictors of sexual dysfunction, even after adjustment for a variety of physical factors. Conclusions Mental distress and sexual dysfunction are extremely common in rheumatologic patients. Sexual dysfunction is significantly associated with anxiety and depression in both men and women and may be independently predicted by their presence in this group of patients. Physicians dealing with rheumatologic patients should be aware of these results and incorporate screening and treatment of the above comorbidities in the global assessment of their patients, in order to alleviate the disease‐emerging mental and physical burden and improve their quality of life. Anyfanti P, Pyrpasopoulou A, Triantafyllou A, Triantafyllou G, Gavriilaki E, Chatzimichailidou S, Gkaliagkousi E, Petidis K, Aslanidis S, and Douma S. Association between mental health disorders and sexual dysfunction in patients suffering from rheumatic diseases. J Sex Med 2014;11:2653–2660.